2016
DOI: 10.1007/s00426-015-0737-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface and structural effects of pitch and time on global melodic expectancies

Abstract: We investigated how the surface and structural information of pitch and time in melodies contribute to the perceived expectancy of melodic segments. The contour (pitch surface), tonality (pitch structure), rhythm (time surface) and metre (time structure) were preserved or altered in factorial fashion, either for the full length of a melody (Full condition) or only its last phrase (Last condition). Participants (N = 24) with a range of musical training received instructions to rate how expected the second porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 92 publications
2
6
0
Order By: Relevance
“…These findings complete prior research on the influence of music on brand perceptions, which has not identified disfluency as a potential influence of brand perceptions. Moreover, echoing extant research (Bigand et al, 2005; Prince & Loo, 2017), the results of this study also confirm that these two music characteristics are key sources of disfluency. Furthermore, they reveal that an irregular contour or unstable tonality can have a negative impact on brand evaluations through increased perceived music disfluency but a positive influence through increased perceptions of innovativeness.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings complete prior research on the influence of music on brand perceptions, which has not identified disfluency as a potential influence of brand perceptions. Moreover, echoing extant research (Bigand et al, 2005; Prince & Loo, 2017), the results of this study also confirm that these two music characteristics are key sources of disfluency. Furthermore, they reveal that an irregular contour or unstable tonality can have a negative impact on brand evaluations through increased perceived music disfluency but a positive influence through increased perceptions of innovativeness.…”
Section: Discussionsupporting
confidence: 88%
“…We created four versions of an 8 s-long sonic logo that could be classified as classical. Employing an established method and adapting stimuli used in prior research (Prince & Loo, 2017), we composed an initial version with a regular contour and stable tonality using music composition software. We created the regular contour by developing a repetitive melody with moderate pitch intervals (for detailed definitions of these characteristics, see Supporting Information: Appendix A).…”
Section: Stimulimentioning
confidence: 99%
“…Palmer and Krumhansl (1987), for example, found that duration and pitch cues carry equal weights in musical phrase perception, without additional benefits from being able to combine the two, while Prince (2014) found that rhythm and melodic contour were independent predictors of melodic similarity judgments, with no interactions between the two. On the other hand, Boltz, 1989a and1989b found an interaction between temporal accent and effects of tonality on perception of resolution at the end of melodies, whereas Prince (2011) and Prince and Loo (2017) found asymmetric interactions between pitch and time: pitch characteristics influenced temporal goodness judgments and expectancy ratings, but temporal characteristics did not influence pitch goodness judgments and expectancy ratings. Our findings support a mixture of independent and interactive accounts of pitch and time processing in music perception.…”
Section: Discussionmentioning
confidence: 92%
“…They were unable to ignore the unattended dimension; interactions were strong when attending to both dimensions. Prince and Loo (2017) found similar failures in selective attention in expectancy ratings. Prince and Pfordresher’s (2012) participants made more reproduction errors in one dimension when the other dimension was more complex.…”
Section: Methodsmentioning
confidence: 64%